DAMPAK PENAMBANGAN PASIR TERHADAP SOSIAL EKONOMI DAN EKOLOGI MASYARAKAT KAWASAN SUNGAI CINDE PARUNGJAYA MAJALENGKA JAWA BARAT - Leli Kudriyati Nisa; Elok Nur Rahmatillah; Nurmazidah Nurmazidah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This research discusses the impact of illegal sand mining in the Cinde River, Parungjaya Village, Majalengka, West Java, on the socio-economic and ecological aspects of the community in the area. This research was motivated by the widespread illegal sand mining activities in the Cinde River which were carried out without permission and supervision from the authorities. It is feared that this activity will have a negative impact on the environment and the lives of the surrounding community. The aim of this research is to analyze the impact of illegal sand mining in the Cinde River on the socio-economic and ecological aspects of the community in the area. Research shows that illegal sand mining in the Cinde River has had a negative impact on the socio-economic and ecological aspects of communities in the area. The socio-economic impacts felt by the community include: loss of sources of livelihood, reduced river water quality, and increased costs of living. The ecological impacts felt include: damage to flora and fauna habitat, soil erosion, and river water pollution.